A BRIEF HISTORY OF DESCRIPTIVE GEOMETRY - Jamilova Dilsuza Tolqin qizi (Bright Mind Publishing, 2025)
The origin and development of the science of descriptive geometry encompasses several stages and historical periods. Studying this subject in more depth helps us understand how interesting and accessible it is, as well as its interrelation with other sciences. We will gain knowledge about the introduction and development of descriptive geometry in our country.